2006
DOI: 10.1590/s0102-79722006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Estresse e suporte social na infância e adolescência relacionados com sintomas depressivos em idosos

Abstract: Resumo Considerando o envelhecimento como período ligado às influências sócio-históricas e experiências ocorridas durante o desenvolvimento, torna-se importante investigar variáveis de outros períodos do curso da vida que possam estar implicadas na saúde dos idosos. Assim, o objetivo deste estudo foi avaliar a relação entre características do suporte social e estresse na infância/adolescência com sintomas depressivos na velhice. Utilizou-se a escala CES-D (Radloff, 1977) e a escala de suporte social e estresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
(5 reference statements)
0
6
0
1
Order By: Relevance
“…Grouping together the 13 studies that reported CSDS, 14,720 elderly people were evaluated with a prevalence that varied between 13% ( Barcelos-Ferreira et al, 2009) and 39% (Castro- Costa et al, 2008) with a combined estimate of 26% (95%CI: 21-32) ( Figure 2). Just two of the 13 studies found a prevalence less than 20% (Lebrão and Laurenti, 2005;Barcelos-Ferreira et al, 2009), and four studies yielded a prevalence greater than 30% (Silberman et al, 1995;Porcu et al, 2002;Cupertino et al, 2006;Castro-Costa et al, 2008). In four studies, a significant association was observed between CSDS and cardiovascular diseases (Silberman et al, 1995;Smith et al, 2005;Blay et al, 2007;Castro-Costa et al, 2008) and between CSDS and female gender (Lebrão and Laurenti, 2005;Costa et al, 2008;Balbé and Garces, 2008;Barcelos-Ferreira et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Grouping together the 13 studies that reported CSDS, 14,720 elderly people were evaluated with a prevalence that varied between 13% ( Barcelos-Ferreira et al, 2009) and 39% (Castro- Costa et al, 2008) with a combined estimate of 26% (95%CI: 21-32) ( Figure 2). Just two of the 13 studies found a prevalence less than 20% (Lebrão and Laurenti, 2005;Barcelos-Ferreira et al, 2009), and four studies yielded a prevalence greater than 30% (Silberman et al, 1995;Porcu et al, 2002;Cupertino et al, 2006;Castro-Costa et al, 2008). In four studies, a significant association was observed between CSDS and cardiovascular diseases (Silberman et al, 1995;Smith et al, 2005;Blay et al, 2007;Castro-Costa et al, 2008) and between CSDS and female gender (Lebrão and Laurenti, 2005;Costa et al, 2008;Balbé and Garces, 2008;Barcelos-Ferreira et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…After excluding overlapping studies and articles that did not evaluate depressive morbidity, the initial set contained 28 studies, of which eight were excluded that used outpatient, hospital, or institutional samples (Almeida et al, 1997;Paradela et al, 2005;Leite et al, 2006;Oliveira et al, 2006;Duarte and Rego, 2007;Borges et al, 2007;Irigaray and Schneider, 2007;Siqueira et al, 2009) and one study in which the authors investigated depression symptoms alone, which did not give an average prevalence that would allow its conclusion in the data analysis (Gazalle et al, 2004). Three studies that worked with the same sample group were analyzed together (Cupertino et al, 2006;Batistoni et al, 2007;Fortes-Burgos et al, 2008), and only the study that yielded information that corresponded to the objective of this research was cited (Cupertino et al, 2006). The final analysis included 17 studies (Table 2): 13 with CSDS, one with major depression alone and three with major depression and dysthymia incorporating a total of 15,491 evaluated elderly patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations